2022
DOI: 10.1186/s12887-022-03191-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of iron overload in a cohort of Sri Lankan patients with transfusion dependent beta thalassaemia and its correlation with pathogenic variants in HBB, HFE, SLC40A1, and TFR2 genes

Abstract: Background Iron overload (IO) is a complication in transfusion dependent beta thalassaemia (TDT). Pathogenic variants in genes involving iron metabolism may confer increased risk of IO. The objective of this study was to determine the magnitude of the cardiac and hepatic IO and determine whether pathogenic variants in HFE, SLC40A1 and TFR2 genes increase the risk of IO in a cohort of TDT patients in Sri Lanka. Materials and Methods Fifty-seven (57)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A similar finding was reported by Dissanayake et al in patients with transfusion dependent βthalassaemia. 25 d. Growth and associated endocrine complications. Only seven patients (3 of Group A and 4 of Group B) had IGF-1 above the 2.5 th percentile of the normal values for the Italian population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was reported by Dissanayake et al in patients with transfusion dependent βthalassaemia. 25 d. Growth and associated endocrine complications. Only seven patients (3 of Group A and 4 of Group B) had IGF-1 above the 2.5 th percentile of the normal values for the Italian population.…”
Section: Resultsmentioning
confidence: 99%
“…A similar finding was reported by Dissanayake et al in patients with transfusion dependent β-thalassaemia. 25 …”
Section: Resultsmentioning
confidence: 99%
“…SLC40A1 (also known as ferroportin) can export iron into interstitial fluid and the general circulation through the basolateral membrane of renal tubular epithelial cells [ 46 ]. SLC40A1 downregulation compromises intracellular iron output, causing iron overload and accelerating cellular ferroptosis [ 47 ]. In this study, we observed that the HG- or PA-induced decrease in HK-2 cell SLC40A1 levels was reversed following dapagliflozin administration.…”
Section: Discussionmentioning
confidence: 99%